2019
DOI: 10.1002/polb.24785
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of a polyfluorene derivative containing complexed neodymium ions

Abstract: Poly[9,9′‐dihexylfluorene‐2,7‐diyl)‐6,6″‐(2,2′:6′,2″‐terpyridine)] (LaPPS75) and its complexes with neodymium were synthesized and characterized. Magnetic measurements showed that the noncomplexed polymer presented a ferromagnetic contribution due to the formation of π stacking, and that in absence of those, the ferromagnetic behavior is suppressed. The pristine polymer, the complexed one and a low‐molecular‐weight model compound with the same structure of the complexed site in the parent polymer were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The polymer (LaPPS59) was prepared through the crosscoupling Suzuki polycondensation and the metallopolymers (LaPPS59Nd / LaPPS59Nd-Cl) were synthesized following reported procedures. [38] A model compound (LaPPS59M) was synthesized to simulate complexed sites as shown in Scheme 1 in Supporting Information.…”
Section: Structural Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…The polymer (LaPPS59) was prepared through the crosscoupling Suzuki polycondensation and the metallopolymers (LaPPS59Nd / LaPPS59Nd-Cl) were synthesized following reported procedures. [38] A model compound (LaPPS59M) was synthesized to simulate complexed sites as shown in Scheme 1 in Supporting Information.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…When the ion is inserted into a conjugated polymer chain, it suffers the influence of high mobile 𝜋 surrounding electrons. The subject has been addressed recently in the literature, [38] but a definitive explanation of the nature of interactions polymer-ion has yet to be found. The experimental results showed that magnetic properties can be very much altered, not only by the presence of the polymer backbone itself but also by the inter-macromolecular interaction forces.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 3 more Smart Citations